ENSURING RESEARCH ON THE ENERGY EFFICIENCY OF BUILDINGS IN EDUCATIONAL INSTITUTIONS (Innovative professional education, 2025)
The need to study the problems of energy efficiency of buildings by future skilled workers is largely due to the complexity of extraction and shortage of basic energy resources, their constantly growing cost, and global environmental problems. The introduction of energy-efficient and energy-saving materials and technologies into the economic activities of enterprises and individuals at the household level will make it possible to solve many environmental problems: climate change, environmental pollution, depletion of natural resources, etc.
Keywords: energy efficiency, skilled workers, environmental problems